Recombinant Activated Factor VII (rFVIIa) in the Management of Major Obstetric Haemorrhage: A Case Series and a Proposed Guideline for Use - Charlotte Bomken; Sue Mathai; Tina Biss; Andrew Loughney; John Hanley (Hindawi Limited, 2009)
Major obstetric haemorrhage remains a significant cause of maternal morbidity and mortality. Previous case reports suggest the potential benefit of recombinant activated factor VII (rFVIIa: NovoSevenR) as a haemostatic agent. We performed a retrospective review of the use of rVIIa in major obstetric haemorrhage in the Northern Region between July 2004 and February 2007. Fifteen women received rFVIIa. The median patient age was 34 years. Major haemorrhage occurred antepartum (5 patients), intrapartum (1), and postpartum (9). All women received an initial dose of 90 mcg/kg rFVIIa and one received 2 further doses. Bleeding stopped or decreased in 12 patients (80%). Additional measures included antifibrinolytic and uterotonic agents, Rusch balloon insertion, uterine curettage/packing, and vessel embolisation. Eight patients required hysterectomy. All women survived to discharge from hospital. No adverse events, including thrombosis, were recorded. This study provides further support for the safety and efficacy of rFVIIa as adjunct therapy in major obstetric haemorrhage.